2021
DOI: 10.1007/s10664-021-09960-w
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of off-the-shelf SE-specific sentiment analysis tools: An extended replication study

Abstract: Sentiment analysis methods have become popular for investigating human communication, including discussions related to software projects. Since general-purpose sentiment analysis tools do not fit well with the information exchanged by software developers, new tools, specific for software engineering (SE), have been developed. We investigate to what extent off-the-shelf SE-specific tools for sentiment analysis mitigate the threats to conclusion validity of empirical studies in software engineering, highlighted … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 43 publications
(89 reference statements)
0
19
0
Order By: Relevance
“…Inspired by the recent advances in deep learning, Biswas et al [11] and Zhang et al [10] also investigated the application of pretrained language models, BERT in particular, in sentiment classification; they found that the BERT sentiment classifier out-performed several other state-of-the-art sentiment analysis techniques on a Stack Overflow dataset. A recent replication study found that Senti4SD has achieved similar performance than BERT-based techniques; the former also out-performed the latter on a GitHub discussion dataset [37].…”
Section: Automated Detection Of Sentiments and Tones In Textmentioning
confidence: 96%
“…Inspired by the recent advances in deep learning, Biswas et al [11] and Zhang et al [10] also investigated the application of pretrained language models, BERT in particular, in sentiment classification; they found that the BERT sentiment classifier out-performed several other state-of-the-art sentiment analysis techniques on a Stack Overflow dataset. A recent replication study found that Senti4SD has achieved similar performance than BERT-based techniques; the former also out-performed the latter on a GitHub discussion dataset [37].…”
Section: Automated Detection Of Sentiments and Tones In Textmentioning
confidence: 96%
“…The second type of task should have shorter text, to evaluate how good the model is for short texts. The third task should be sentiment mining, as a general domain use case that is already well understood in the SE domain [15], incl. strong, already existing results that general domain transformer models are the current state-ofthe-art for sentiment mining in the SE domain [14].…”
Section: Fine-tuned Prediction Tasksmentioning
confidence: 99%
“…Additionally, we also consider sentiment mining as fine-tuning task, a task where it was already shown that general domain transformers perform well [14]. Since sentiment mining possibly also works on SE domain data without SE domain knowledge [15], the evaluation of this tasks allows us to understand if even tasks that are not SE specific can be improved with SE domain transformers.…”
Section: Introductionmentioning
confidence: 99%
“…However, our results do not contain enough data on sentiment analysis tools based on neural networks to draw conclusions about them. Nevertheless, according to the latest developments, this neural network approach delivers promising results [58,79].…”
Section: Future Research Directionsmentioning
confidence: 99%
“…In Section 5, we discuss our results, before concluding the paper in Section 6. described models based on the neural network BERT [14], which were trained with data related to SE such as GitHub 3 or Stack Overflow 4 . In their replication study, Novielli et al [58] explained some sentiment analysis tools (e.g. Senti4SD [8]) in great detail and described the underlying data.…”
Section: Introductionmentioning
confidence: 99%